Tautomers of N-acetyl-d-allosamine: an NMR and computational chemistry study - Plazinski Wojciech; Roslund Mattias U; Sawen Elin; Engström Olof; Tähtinen Petri; Widmalm Göran (ROYAL SOC CHEMISTRY, 2022)
d-Allosamine is a rare sugar in Nature but its pyranoid form has been found alpha-linked in the core region of the lipopolysaccharide from the Gram-negative bacterium Porphyromonas gingivalis and in the chitanase inhibitor allosamidin, then beta-linked and N-acetylated. In water solution the monosaccharide N-acetyl-d-allosamine (d-AllNAc) shows a significant presence of four tautomers arising from pyranoid and furanoid ring forms and anomeric configurations. The furanoid ring forms both showed (3)J(H1,H2) approximate to 4.85 Hz and to differentiate the anomeric configurations a series of chemical shift anisotropy/dipole-dipole cross-correlated relaxation NMR experiments was performed in which the alpha-anomeric form showed notable different relaxation rates for its components of the H1 doublet, thereby making it possible to elucidate the anomeric configuration of each of the furanoses. The conformational preferences of the different forms of d-AllNAc were investigated by (3)J(HH), (2)J(CH) and (3)J(CH) coupling constants from NMR experiments, molecular dynamics simulations and density functional theory calculations. The pyranose form resides in the C-4(1) conformation and the furanose ring form has the majority of its conformers located on the South-East region of the pseudorotation wheel, with a small population in the Northern hemisphere. The tautomeric equilibrium was quite sensitive to changes in temperature, where the beta-anomer of the pyranoid ring form decreased upon a temperature increase while the other forms increased.